CHANGE OF THE PATTERN OF PLAY CHILDREN (Case Studies: School Age Children In Nagari Koto Nan Duo Kecamatan Batang Kapas Kabupaten Pesisir Selatan) - Yupipit, Isrila Welly; Melia, Yenni; Rahmad, Darmairal (Pendidikan Sosiologi, 2014)
The background of the research is there many children in Nagari Koto Nan Duo prefer play traditional games to modern games. As developing of modern games nowadays, the traditional has been forgotten by many children. The research aims are 1) to describe the change form of childrenâ playing pattern and 2) to describe the impacts of the changes of childrenâs play at Nagari Koto Nan Duo Kecamatan Batang Kapas Kabupaten Pesisir Selatan. The theory used in this research is functionalist theory from William Ogburn. Research method used is qualitative approach with descriptive type. Informan taken technique is done by purposive sampling way with 24 people. Data found are primary and secondary form. The data collected by using interviewing technique, observing, and documentation with analysis unit, group. The data is analyzed using Miles and Huberman technique consist of 3 stage; data reduction, data presentation, and conclusion/data verification. Result of the research shows that change of children play can be seen a) by location, b) time, c) form, d) frequency and collectivity. The children at Nagari Koto Nan Duo seem playing more modern games rather the traditional ones. It is proven that the frequency of playing modern game is higher than traditional. It affects children behavior which makes they play individually at home even though play outside they just play with two person only. Another impact is children addicted playing modern game. It influences childrenâ concentration to study at school. The children are getting lazy and jus t thinking about playing game soon after school. Moreover, it affect an extra budget needed which makes them lie to their parents to get more money for playing game.